C-Abl contributes to glucose-promoted apoptosis via p53 signaling pathway in podocytes. (March 2016) - Ma, Yiqiong; Yang, Qian; Chen, Xinghua; Liang, Wei; Ren, Zhilong; Ding, Guohua
Highlights: Expression of c-Abl in podocytes is up-regulated in the condition of high glucose. c-Abl contributes to high glucose-induced apoptosis of podocytes. Pro-apoptosis factor p53 is involved in c-Abl signaling in the process of podocytes apoptosis. Abstract: Aim: To investigate the role of the non-receptor tyrosine kinase c-Abl in high glucose-induced podocyte injury and its possible signal transduction pathway. Methods: Sixteen C57BL/6 mice were randomly assigned to a group with diabetes and a normal control group. Subsequently, differentiated mouse podocytes were exposed to high-glucose conditions, and podocyte apoptosis was then assessed by flow cytometry and Hoechst 33258 staining. Western blot and immunofluorescence assay were used to measure c-Abl expression. Co-immunoprecipitation assay was used and c-Abl siRNA was applied to evaluate the interaction between c-Abl and p53. Results: High glucose promotes podocyte apoptosis. The c-Abl expression in podocytes was increased after exposure to high glucose, stimulating the p53 signaling pathway. Conversely, treatment with c-Abl siRNA restored high glucose-promoted podocyte apoptosis and resulted in the reduction of p53 expression . Conclusion: c-Abl contributes to high glucose-induced podocyte apoptosis via p53 signaling pathway.